2008
DOI: 10.1136/hrt.2008.146548
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of left atrial longitudinal function in patients with hypertrophic cardiomyopathy: a tissue Doppler imaging and two-dimensional strain study

Abstract: Left atrial longitudinal function is reduced in HCM compared to non-HCM LVH and healthy controls. In addition, 2D atrial strain has an additive value in differentiating HCM from non-HCM LVH and it is more reproducible and less time consuming than TDI strain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(72 citation statements)
references
References 49 publications
4
61
0
6
Order By: Relevance
“…21 One study in 50 HCM patients indicated that LA reservoir speckle tracking-derived strain independently predicts occurrence of AF requiring hospitalization (odds ratio, 0.85; 95% . 24 The present study, representing the largest cohort of HCM patients evaluated by LA strain to date, demonstrates higher sensitivity of LA strain compared with LA diameter to predict new-onset AF and confirms its independent predictive value for this end point.…”
Section: Discussionmentioning
confidence: 57%
“…21 One study in 50 HCM patients indicated that LA reservoir speckle tracking-derived strain independently predicts occurrence of AF requiring hospitalization (odds ratio, 0.85; 95% . 24 The present study, representing the largest cohort of HCM patients evaluated by LA strain to date, demonstrates higher sensitivity of LA strain compared with LA diameter to predict new-onset AF and confirms its independent predictive value for this end point.…”
Section: Discussionmentioning
confidence: 57%
“…'Strain' görüntüleme SA fonksiyonlarının değerlendirilme-sinde de oldukça değerlidir. Doku Doppler ve iki boyutlu "strain" ile yapılmış incelemelerde atrium fonksiyonlarının HKM hastalarında diğer ikincil nedenlerle ilişkili hipertrofi hastalarına göre daha fazla azaldığı gösteril-miştir (32). "Strain" ekokardiyografinin HKM'li hastalarda prognozun belirlemesindeki yeri şu an için net olarak bilinmemektedir.…”
Section: Strain (Gerilme) Görüntülemeunclassified
“…U pacjentów z HCM podłużne odkształcenie ścian LA jest wyraźnie obniżone, zarówno w fazach biernych (rezerwuarowej i okresie wczesnorozkurczowym), jak i czynnej (skurcz LA). Zmiany te są bardziej zaawansowane niż u chorych z wtórną przebudową LA, co może wskazywać na pierwotny remodeling jego ściany [78].…”
Section: Powiększenie Lewego Przedsionkaunclassified